Multi Sensor-Based Obstacle Avoidance Algorithm in Visual Engineering Environment - Abqori Aula (ELKHA : Jurnal Teknik Elektro, 2022)
Obstacle avoidance is an essential problem for applications involving multiple wheeled mobile robots. This research proposes a simple obstacle avoidance rule utilizing only one type of sensor, i.e., infrared sensor. In this research, multiple infrared sensors are placed on a mobile robot, arranged 45° radially equidistance. By using a low-cost and easily available infrared sensor, the cost and time consumed to build and repair a wheeled mobile robot are considerably reduced. Avoiding rules, based on simple behavior, such as “turn”, “stop”, “follow”, and “ignore” are developed. By applying these rules, each robot can refer to the motion of other robot or stationary object to avoid collision. Simulation results show that the proposed algorithm performs well, at 66.7% chance of avoiding a moving object and at 93% chance of avoiding a stationary object.